ESG and Financial Performance in Enhancing Banking Firm Value: A Study of Banks Listed on the Indonesia Stock Exchange (IDX) - Beta Kurnia; Zaenal Abidin (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study aims to analyze the effect of sustainability, intermediation efficiency, credit risk, and profitability on the firm value of banking companies listed on The Indonesia Stock Exchange (IDX) during the 2021-2024 period. Firm value is measured using Tobin's Q while sustainability, intermediation efficiency, credit risk and profitability proxied by ESG score, Net Interest Margin (NIM), Non-Performing Loan (NPL), and Return on Asset (ROA). This study uses quantitative method with panel data regression analysis, and the data are processed using Eviews. The sample in this study is selected using purposive sampling, resulting in 13 banking companies as the final sample. The results of this research show that partially, ESG and NIM do not have a significant effect on firm value, NPL has a significant negative effect on firm value, and ROA has a significant positive effect on firm value. Meanwhile, simultaneously, ESG, NIM, NPL, and ROA have a significant effect on firm value. These findings show that financial and non-financial indicators can play a role in affecting firm value in the banking sector.